Pulmonary Adenocarcinoma Occurring 5 Years after Resection of a Primary Pancreatic Adenocarcinoma: A Relevant Differential Diagnosis - R. F. Falkenstern-Ge; M. Wohlleber; M. Kimmich; K. Huettl; G. Friedel; G. Ott; M. Kohlhäufl (Case Reports in Oncological Medicine)
Ductal adenocarcinoma of the pancreas is a lethal disease. Surgical extirpation only offers the slim chance for long-term survival in localized disease. We report on a 73 year old female patient who initially underwent successful resection of pancreatic adenocarcinoma in May 2005. She was treated with adjuvant chemotherapy with gemcitabine. In October 2010 the patient noticed increasing dyspnea with haemoptysis. She was soon referred to our center. After the diagnosis of pulmonary adenocarcinoma with widespread metastasis, she was treated with systemic chemotherapy. For a period of next three years, she was treated with different chemotherapy regimens due to repeated episodes of tumor progression. To the best of our knowledge after reviewing the literature, this case represents an unusually clinical course with metachronous pulmonary adenocarcinoma arising after treatment of a primary pancreatic cancer after a long latency period.